Pedagogical experiences through pibid: reports and experiences in teaching geography - Pessetti, Mateus; Lino, Cristian Guilherme (Revista Ensino de Geografia (Recife), 2021)
This article presents a reflection and a report from the experiences and practices experienced through the Institutional Program for Teaching Initiation Scholarships - PIBID. To this end, a brief theoretical discussion was held regarding the teaching of geography and school cartography. Subsequently, two practices developed with students from an elementary school in the city of Passo Fundo / RS were reported, where the subproject PIBID - Geography of the University of Passo Fundo is inserted. The increase in PIBID in teacher training institutions, provides an opportunity to bring academic and school knowledge closer together. It is necessary to provide opportunities for the knowledge produced within these institutions to be in line with society, especially with the school environment when it comes to teacher training. In addition to highlighting the importance that PIBID has for teacher training, the need for adequate practices for effective cartographic literacy was highlighted, thus developing skills in orientation, localization and the decoding of cartographic language